"Rememory" and meaning: the narrative of a mother giving birth to her own subjective identity through weblog writing. Issue 2 (3rd April 2017) - Rottenberg, Biri; Schonmann, Shifra; Berman, Emanuel
ABSTRACT: The narratives of mothers are usually not expressed through cultural and national memories. In addition, the psychological theories insist on defining motherhood and subjectivity from the point of view of the developing child. The term "subjective motherhood" enables us to attempt to describe and theorize maternal subjectivity in this complicated and contradictory sense. The aim of this research is to create a wide enough concept of motherhood subjectivity in order to contain the motherhood experience as a process of creating identity and meaning. The blog "this is the way I am" is the room of Pema, a 49 year old Israeli mother and the author of a weblog. The written narratives in her blog reflect the dialogue between the mental dimensions of rememory and meaning. Through the writing process, Pema is giving narrative birth to her subjective identity as a mother. Writing a blog gave Pema the most precious thing she owns, the story of her subjectivity.